Clinical interviewing [includes DSM-5 coverage] - Sommers-Flanagan, John 1957-; Sommers-Flanagan, Rita 1953- (Wiley, 2014)
"Becoming an effective interviewer is as much an art as it is a science. Now fully revised and updated, Clinical Interviewing, Fifth Edition reveals both the scientific basis and interpersonal aspects of mental health interviewing. Presenting a clear and instructive picture of how to interview clients in therapy, the new edition of this bestselling text reflects current research and includes important expansion of multicultural content throughout. Graduate students in social work, counseling, and psychology will gain insight into, and practical examples of, useful interviewing techniques for more effective therapy"..